EXPLORING IMPLICATURE OF MAXIM VIOLATION IN THE U.S. VICE PRESIDENTIAL DEBATE - Ela Martisa; Siti Munawwarah; Rahmawati Azi; La Ino (Program Studi Pendidikan Bahasa Inggris, 2024)
In political communication, maxim violation as well as its implicature are inevitable. It shows a dynamic of communication particularly how to influence audience perception through argumentative strategies. This study tries to explore the maxim violation and implicature performed by Mike Pence and Kamala Harris in the U.S. Vice Presidential Debate in 2020. The study applied the cooperative principle theory particularly maxim violation and implicature by Paul Grice. Descriptive qualitative method was employed through the research. The main source of the data are the utterances of both vice Presidents’candidates which contain violation of maxim and implicature. The result shows that during the debate, there were 10 data of maxim quantity, 3 data of maxim quality, 6 maxim of relevance, and 1 data of maxim of manner. Violation of the maxim of quantity is the most common in the debate. because the candidates giving answers that seem exaggerated to, giving answers that are somewhat not so clear and irrelevant answers to distract the public. It also reveals that generalized conversational implicature is dominant used because political communication is highly context-dependent, and politicians frequently need to convey nuanced messages without being too direct.